Environmental Ethics in Ancient Javanese Philosophy: Reconstructing the Concept of Rahayu as a Local Ecosophy - wijaya wijaya; Yohanes Kamakaula; Bagus Ardiyansyah; Ravi Dara (Journal of Humanities Research Sustainability, 2024)
Background. Global environmental destruction is driving the search for alternative environmental ethics that is not only universal but also rooted in local wisdom. Ancient Javanese philosophy holds the concept of Rahayu which represents the harmony of the cosmos and the principle of sustainability. Purpose. This research aims to reconstruct the concept of Rahayu as a relevant framework for local ecosophy to answer contemporary ecological challenges. Method. The hermeneutical approach is used to analyze ancient manuscripts, oral traditions, and cultural practices related to Rahayu. Interviews with cultural sources and literature studies support philosophical and ecological interpretations. Results. Research has found that Rahayu contains the principles of cosmological balance, respect for nature, and resource sustainability. This value is in line with modern environmental ethics but is firmly rooted in Javanese agrarian cosmology. Conclusion. Rahayu's reconstruction produces a framework for local ecosophy that has the potential to be applied in education, policy, and environmental social movements. This concept can bridge traditional knowledge and global environmental ethical theory. This research offers a unique integration between modern environmental philosophy and Javanese local wisdom through the Rahayu concept, while presenting an analytical method that combines philosophical, anthropological, and cultural ecological approaches.